2014
DOI: 10.1111/sms.12186
|View full text |Cite
|
Sign up to set email alerts
|

Muscle conduction velocity, strength, neural activity, and morphological changes after eccentric and concentric training

Abstract: This study compared the effects of concentric and eccentric training on neuromuscular adaptations in young subjects. Twenty-two men and women were assigned to one of two groups: concentric (CON, n = 11) and eccentric (ECC, n = 11) training. Training consisted of 6 weeks of isokinetic exercise, performed twice weekly, starting with two sets of eight repetitions, and progressing to five sets of 10 repetitions. Subjects were tested in strength variables [concentric, eccentric, and isometric peak torque (PT), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 46 publications
7
73
0
5
Order By: Relevance
“…Statistical significance for all tests was accepted at P < 0.05. 23,31,32 To ensure adequate statistical power for all analyses, power analysis was conducted for tendon stiffness (ie, the variable with the smallest effect size) using the following parameters (variable = tendon stiffness, power = 0.80, alpha = 0.05, effect size = 1.1, attrition = 20%). The analysis revealed that the total sample size required for statistical power was 22, thus 28 subjects were initially recruited to account for possible attrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical significance for all tests was accepted at P < 0.05. 23,31,32 To ensure adequate statistical power for all analyses, power analysis was conducted for tendon stiffness (ie, the variable with the smallest effect size) using the following parameters (variable = tendon stiffness, power = 0.80, alpha = 0.05, effect size = 1.1, attrition = 20%). The analysis revealed that the total sample size required for statistical power was 22, thus 28 subjects were initially recruited to account for possible attrition.…”
Section: Discussionmentioning
confidence: 99%
“…Effect sizes (Cohen's D ) were calculated from mean changes in variables (strength [ES = 1.65], hypertrophy [ES = 1.58], creatine kinase [ES = 3.95], ROM [ES = 1.78], tendon stiffness [ES = 1.10], elastic energy storage [ES = 1.88], and peak passive moment [ES = 2.11]) from previous studies employing similar interventions . To ensure adequate statistical power for all analyses, power analysis was conducted for tendon stiffness (ie, the variable with the smallest effect size) using the following parameters (variable = tendon stiffness, power = 0.80, alpha = 0.05, effect size = 1.1, attrition = 20%).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of muscle quality, such as echo intensity (EI), are indicative of a muscle's fat and fibrous tissue content (Pillen et al 2009) and may also be potentially useful for assessing traininginduced increases in strength-related performances (Cadore et al 2014;Fukumoto et al 2013;Radaelli et al 2014). For example, Cadore et al (2014) recently reported that increases in maximal torque production after 6 wk of isokinetic training were significantly related to improvements in EI, which suggests that training-induced increases in muscle quality are linked to improvements in maximal strength. In light of these findings and given the potential contribution of CSA, MT and EI to measures of maximal and explosive strength and other functionally important parameters, recent research studies have heavily focused on identifying highly sensitive and reliable non-invasive imaging techniques for assessing muscle size and quality measurements (Caresio et al 2014;Melvin et al 2014;Rosenberg et al 2014;Strandberg et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…As a result, it has been suggested that muscle size measurements, such as cross-sectional area (CSA) and muscle thickness (MT), may be used as an indirect method to predict changes in maximal and/or explosive strength (Cormie et al 2010). Measurements of muscle quality, such as echo intensity (EI), are indicative of a muscle's fat and fibrous tissue content (Pillen et al 2009) and may also be potentially useful for assessing traininginduced increases in strength-related performances (Cadore et al 2014;Fukumoto et al 2013;Radaelli et al 2014). For example, Cadore et al (2014) recently reported that increases in maximal torque production after 6 wk of isokinetic training were significantly related to improvements in EI, which suggests that training-induced increases in muscle quality are linked to improvements in maximal strength.…”
Section: Introductionmentioning
confidence: 99%
“…This result is different from those of previous studies. Cadore et al [36] reported a similar increase after 6 weeks of ECT and CCT in the VL MT of twenty-two healthy adults. In the study by Norrbrand et al [37], 15 healthy adults performed ECT and CCT for 5 weeks and MT increases of the quadriceps in the ECT group was reported, though the increase was not significant.…”
Section: Discussionmentioning
confidence: 70%